Research on the Particle Growth Process of Colloidal Silica Derived from the Sol-Gel Process Using Active Silicic Acid Solutions - Kazuaki Higuchi; Yujia Liu; Masafumi Unno (Solids)
The influence of the quantity of silanol in an active silicic acid solution (ASAS) on the growth rate of colloidal silica particles was investigated. The quantity of silanol in the ASAS was controlled by varying the acid concentration as a hydrolysis catalyst for tetramethoxysilane (TMOS). As expected, the particle growth rate was confirmed to be a function of the acid concentration in the water used to prepare the ASAS. In addition, when the entire process was conducted under basic conditions to obtain spherical particles, the initial basicity had a secondary influence on the particle growth rate. When a partial process was conducted under acidic conditions to obtain morphologically modified particles, the low acidity was found to have a secondary influence on the particle growth rate. Furthermore, it was clarified that the relative silica deposition rate based on acid-free ASAS could be predicted by assuming the seed particle size at the time it was determined. Thus, a production control system was established for highly purified colloidal silica using ASAS derived from TMOS.